2023
DOI: 10.3390/cells12020226
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tau Expression in Superior Cervical Ganglion (SCG) Neurons In Vivo and In Vitro

Abstract: The superior cervical ganglion (SCG) is part of the autonomic nervous system providing sympathetic innervation to the head and neck, and has been regularly used to prepare postnatal neuronal cultures for cell biological studies. We found that during development these neurons change tau expression from the low molecular weight (LMW) isoforms to Big tau, with the potential to affect functions associated with tau such as microtubule dynamic and axonal transport. Big tau contains the large 4a exon that transforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…After the original discovery and cloning of Big tau in the early 90's (Couchie et al, 1992;Goedert et al, 1992), there has been a long pause in the study of Big tau properties. It was only in the last few years that the interest resumed with reports on its developmental regulation and evolutionary history (Fischer, 2022;Jin et al, 2023) as well as discovering the expression of Big tau in non-neural peripheral tissue such as Heart (Luciani et al, 2023), lung (Choi et al, 2022) and submandibular gland (Hamsafar et al, 2023) with implications on tau aggregation and function relative to LMW tau (Fischer & Baas, 2020;Fischer, 2023). Here we focused our attention to the visual system, considering early studies that reported a form of Big tau with a middle MW (Mercken et al, 1995), with the goal of elucidating the structure and expression in a complex but well define CNS system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the original discovery and cloning of Big tau in the early 90's (Couchie et al, 1992;Goedert et al, 1992), there has been a long pause in the study of Big tau properties. It was only in the last few years that the interest resumed with reports on its developmental regulation and evolutionary history (Fischer, 2022;Jin et al, 2023) as well as discovering the expression of Big tau in non-neural peripheral tissue such as Heart (Luciani et al, 2023), lung (Choi et al, 2022) and submandibular gland (Hamsafar et al, 2023) with implications on tau aggregation and function relative to LMW tau (Fischer & Baas, 2020;Fischer, 2023). Here we focused our attention to the visual system, considering early studies that reported a form of Big tau with a middle MW (Mercken et al, 1995), with the goal of elucidating the structure and expression in a complex but well define CNS system.…”
Section: Discussionmentioning
confidence: 99%
“…There is also clinical evidence of relatively more resistance or delay of neurodegeneration of PNS neurons relative to CNS neurons. Things started to get more complex when even in PNS the expression of Big tau in DRG neurons was shown to be selective to small and medium size cells and the finding that at early developmental stages SCG neurons expressed only the LMW forms and then switch to express Big tau postnatally (Jin et al, 2023). Further analysis discovered that in the CNS there are specific regions such as the cerebellum and the visual system that express Big tau (Boyne et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By E18 Big tau is already present in rat DRGs but appears only in a subset of small and medium size neurons as well as the dorsal roots. By early postnatal (P2) Big tau expression increases, while LMW tau decreases reaching adult levels by P14 where the dominant form is Big tau, which remains in a selective distribution of small and medium sized neurons (IB4 and CGRP-positive), but not large neurons (parvalbumin-positive) (Jin et al, 2023).…”
Section: Sensory Neurons (Drg)mentioning
confidence: 99%
“…Interestingly all the neurons in adult SCG express Big tau at the expected 110 kDa. Experiment with SCG explants show that in response to a lesion Big tau extends gradually along the regrowing neurites suggesting that it does not drives regeneration but facilitates the structure/function of mature SCG neurons (Jin et al, 2023). These data are consistent with the sciatic nerve regeneration data that showed that the levels of Big tau protein decreased in the DRG following axotomy (Oblinger et al, 1991).…”
Section: Where Is Big Tau Expressed?mentioning
confidence: 99%